Behavioral disorders practice concerns and students with EBD - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Bingley, U.K. : Emerald, 2012)
The area of behavioral disorders is constantly changing and advancing as a result of legislation, new trends, and current research investigations. Currently, there is no comprehensive resource that effectively covers these advances with the breath of topics as this volume. Though it is difficult to keep up with all issues and trends, this volume presents critical topics in all spheres of this area of study.
Preface / Jeffrey P. Bakken, Festus E. Obiakor, Anthony F. Rotatori -- ch. 1. Inclusion and students with emotional and behavioral disorders / Richard Simpson, Nancy A. Mundschenk -- ch. 2. Academic instruction and students with emotional and behavioral disorders / Jessica L. Hagaman -- ch. 3. Social skills training and students with emotional and behavioral disorders / Kathryn J. Casey -- ch. 4. Effective practices/interventions for students with emotional and behavioral disorders / Stacey Jones Bock, Christy Borders -- ch. 5. Positive behavior supports and students with emotional and behavioral disorders / Douglas Cheney, Kelly Jewell -- ch. 6. Response to intervention (RtI) and students with emotional and behavioral disorders / James M. Kauffman, Andrew Bruce, John Wills Lloyd -- ch. 7. Mental health issues and students with emotional and behavioral disorders / Kendra P. DeLoach, Melissa Dvorsky, Elaine Miller, Michael Paget -- ch. 8. Promising practices for effective transition for students with emotional and behavioral disorders / Antonis Katsiyannis, Dalun Zhang, Sara Moore Mackiewicz -- ch. 9. Technology and students with emotional and behavioral disorders / Carrie Anna Courtad, Emily C. Bouck -- ch. 10. Families and students with emotional and behavioral disorders / Fredrick J. Brigham, Jeffrey P. Bakken, Anthony F. Rotatori -- ch. 11. Teacher preparation and students with behavioral disorders / Diane M. Myers, Brandi Simonsen, George Sugai.
Print version record
Keywords: Education -- Special Education -- Learning Disabilities; Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Teaching of students with emotional & behavioural difficulties; Special education; Behavior disorders in children; Behavior disorders in adolescence